The examination of the profit-making capacity of the wooden chip-based large-scale product path - Durkó, Emília (Acta Agraria Debreceniensis, 2015)
Heating with wooden chips would provide a significantly cheaper energy production alternative for the local governments in heating their facilities and in district heating as well. The raw material should be available in the appropriate quality, quantity and at the right time. This type of heating requires the well-organized and joint work of the forestry, transporting, processing and receiving plants. This activity might be realized in the form of non-profit clusters. In order not to suffer any losses, the participants of the product path should carry out a very careful planning regarding the factors appearing in heating with wood but missing from gas heating. One such critical element is the transportation distance which might make the basically cost-efficient wooden chip-based heating process significantly more expensive. One of the main findings of my paper is that the transportation distance should be at most 23 kilometers for the wooden chips to be worth (economical) using against gas. From the viewpoint of practical use, this can be interpreted as the distance between the forestry and heatproducing units. By determining the constant and varying costs of transporting and chopping and from calculating the initial contribution, I concluded that the profit-making capacity of the product path would be sufficient for an energy-related investment. According to my calculations, by remaining within the economical transporting distance of 23 kilometers, such long-term savings might be achieved compared to gas heating which would partly cover the establishment of a biomass-based power plant or heating plant.